Micro-tribological performance of fullerene-like carbon and carbon-nitride surfaces - Flores-Ruiz, F.; Tucker, Mark; Bakoglidis, K.; Yu, X.; Gellman, A.; Herrera-Gomez, A.; Hultman, L.; Rosen, J.; Broitman, E. (Pergamon, 2018)
We studied the microtribological behavior of amorphous and fullerene-like (FL) carbon and carbon-nitride coatings deposited by filtered-cathodic-arc. All films show similar friction coefficients but different wear mechanisms. The FL films exhibit a surface swelling with the formation of a layer that thickens during the test, limiting wear and maintaining a low friction. X-ray photoelectron spectroscopy on worn FL film surfaces show an increase in the sp2-content, indicating that the lubricious layer generated by the wear process is probably the result of re-hybridization due to plasticity induced by localized shear. In contrast, the wear results of the amorphous films, involving tribomechanical and tribochemical surface phenomena, show that the surface layer formed during sliding is a precursor to the onset of wear.